Northward-propagating nighttime medium-scale traveling ionospheric disturbances observed with SuperDARN Hokkaido HF radar and GEONET - Ichihara, Akimitsu; Nishitani, Nozomu; Ogawa, Tadahiko; Tsugawa, Takuya (Polar Research Institute of China - PRIC, 2013)
We report on the characteristics of nighttime medium-scale traveling ionospheric disturbances (MSTIDs) propagating northward observed with the SuperDARN Hokkaido HF radar, which has a field of view to the north of Japan, and occasionally with the GNSS Earth Observation NETwork (GEONET), which provides total electron content (TEC) data over Japan. From statistical analysis of MSTIDs observed with the Hokkaido radar during nighttime (1700–0700 LT) from January 2007 to July 2009, we find that these MSTIDs traveling northward, although rare in comparison with those traveling southwestward, have a relatively high occurrence rate after sunset and around midnight in May and August, which is partly consistent with the occurrence rate of MSTIDs over Japan observed with GEONET in 2002, when the MSTID event database is available. We also use the data from simultaneous observation of nightside MSTIDs by the Hokkaido radar and GEONET to find that when the HF radar observed northward-propagating MSTIDs, GEONET did not always observe such MSTIDs with the same propagation direction. Judging from this result and considering the HF radar field of view located to the north of the GEONET coverage area, we speculate that some physical parameters of the ionosphere/thermosphere over Japan differ from those to the north of Japan, which may result in the inconsistency of MSTID propagation direction. The present results provide new knowledge of MSTIDs propagating northward using the Hokkaido radar, whose field of view was not covered by GEONET.